Pengolahan Citra Satelit dalam Deteksi Alih Fungsi Hutan Pada Daerah Aliran Sungai Arut Kabupaten Kotawaringin Barat Provinsi Kalimantan Tengah Berbasis Sistem Informasi Geografis - Hanindito, Gregorius Anung (UNIVED Press, 2019)
West Kotawaringin Regency is one of the districts in the Central Kalimantan region which is geographically drained by 3 (three) large rivers, namely: the Kumai River, the Lamandau River and the Arut River. As time goes by and population density increases, the existence of rivers creates new problems due to the development and expansion of agriculture and plantations. Referring to this problem, this research was conducted to observe the level of land cover change that occurred in the Arut river basin, South Arut District, West Kotawaringin Regency. This research was carried out using remote sensing methods and geographic information systems. The data used in this method is Landsat satellite image data from 1996, 2010 and 2016. These three data are classified according to their appearance using the supervised classification method and analyzed using the intersection technique. The restrictions on conversion of functions in this research were only carried out on the appearance of forests and plantations. This research produced a map of changes in forest conversion to plantations in the 1996-2016 time period. This research also produces patterns of changes in forest and plantation areas during this time period.